Functional Specialization within the EXO70 Gene Family in Arabidopsis - Marković, Vedrana; Kulich, Ivan; Žárský, Viktor (International journal of molecular sciences, 2021)
Localized delivery of plasma-membrane and cell-wall components is a crucial process for plant cell growth. One of the regulators of secretory-vesicle targeting is the exocyst tethering complex. The exocyst mediates first interaction between transport vesicles and the target membrane before their fusion is performed by SNARE proteins. In land plants, genes encoding the EXO70 exocyst subunit underwent an extreme proliferation with 23 paralogs present in the Arabidopsis (Arabidopsis thaliana) genome. These paralogs often acquired specialized functions during evolution. Here, we analyzed functional divergence of selected EXO70 paralogs in Arabidopsis. Performing a systematic cross-complementation analysis of exo70a1 and exo70b1 mutants, we found that EXO70A1 was functionally substituted only by its closest paralog, EXO70A2. In contrast, none of the EXO70 isoforms tested were able to substitute EXO70B1, including its closest relative, EXO70B2, pointing to a unique function of this isoform. The presented results document a high degree of functional specialization within the EXO70 gene family in land plants.
Keywords: buněčná membrána; EXO70A1; Arabidopsis; vezikulární transportní proteiny; proteiny huseníčku; Transport Vesicles; exocyst complex; Cell Membrane; EXO70; Arabidopsis Proteins; EXO70B1; polar exocytosis; transportní vezikuly; Vesicular Transport Proteins; regulace genové exprese u rostlin; exocytóza; Exocytosis; Gene Expression Regulation, Plant